Solar ultraviolet radiation in South Africa: clinical consequences for the skin. (December 2013) - Wright, Caradee Y; Davids, Lester M; Summers, Beverley; Norval, Mary
Due to its latitude, topography and cloudless skies, South Africa receives high solar ultraviolet radiation (UVR). This country has a multi-ethnic population classified into black, colored, Asian and white groups, who have varying degrees of response to sun exposure. In this review, information relating to the effects of solar UVR on skin cancer development, oculocutaneous albinism, melasma, the immune system and vitamin D production are discussed in the context of the peoples of South Africa. Methods of personal photoprotection are included. Effective sun safety messages for the public need to be developed, particularly aimed at the most susceptible groups, while recognizing the issues associated with variations in skin color in the South African population.